Labile fraction changes of soil organic matter along the gradients of altitude in drylands with dry climate - Andy Wijanarko; Agustina Asri Rahmianna (Brawijaya University, 2019)
Labile fraction plays a crucial role in maintaining soil fertility. Until recently, the information on the labile fraction of soil organic matter in dry lands with dry climates of Indonesia is very limited. Therefore, the experiment was conducted to study the changes of a labile fraction of soil organic matter in those drylands. The soil samples were obtained from 4 sub-districts (Kanatang, Haharu, Pandawai, and Matawai La Pawu) of Sumba Timur District. Those sub-districts have different altitudes, i.e. from 25 m – 900 m above sea level (asl). Soil samples were taken at 0-20 cm soil depth. Chemical analysis on soil pH, total N, organic C, and labile fractions analysis (water-soluble fraction, microbial biomass C, particulate organic matter, and microbial biomass N and water-soluble N) was done at The Plant and Soil Analytical Laboratory of ILETRI. The results indicated that altitude affected the availability of total N and organic C in soils. The higher the altitudes, the lower were N concentrations and conversely for the concentration of organic C and C:N ratio. Labile fraction N (water-soluble N and microbial biomass N) was reduced by increasing the altitudes. The ratio of labile fraction/organic C at altitudes >700 m asl was higher. This meant that the concentration of the active carbon pool was higher compared to that at altitudes <700 m asl. The ratio of MBC/SOC, as the indicator for the rate of biological activity, at altitudes >700 m asl was also high. The high value of MBC/SOC showed that the conversion of soil organic matter to microbial C was efficient.